Grand central staircase flanked by pair of Chimeras - Ghosh, Ayan (Jio Institute, 2023)
Highlight of the BMC building is its spectacular central hall that greets visitors as they enter through the porte cochere. The hall is located directly below the inner dome and serves as an atrium, through which a grand staircase rises, flanked by a pair of winged lions. The staircase winds up to connect arcaded corridors that runs around the hollow central core.